KAJIAN YURIDIS PELAKSANAAN PENINGKATAN HAK GUNA BANGUNAN MENJADI HAK MILIK UNTUK RUMAH TINGGAL DI KANTOR PERTANAHAN KABUPATEN SUKOHARJO - SASANA, SOERYANTARA ADHI (Dinamika Hukum, 2016)
Conclusion. The grant of Freehold Title on Land for Residence in Sukoharjo Regencywas finally produced. It had been suitable with the Rule of law which ruled the implementation of of the upgrading of building right title into freehold title for residence at the Land Agency Office ofSukoharjo Regency. The legal consequenceon the grand had a legal evidence in the form of certificate and had a legal forcein the constellation of agrarian law. The inhibiting factor was caused by the limitation of personnel or the officials of measurement and the officials of sketching using a computer system which was unbalanced by the amount of the first request of land registration sporadically at the Land Agency Office of Sukoharjo. It had an impact on the delay of the finishing of measurement tasks, the making of situation sketch, and the making of land surface sketch using a computer system. Keywords: The Upgrading of Building Right Title, Legal Certainty.